AESTHETIC TOURISM AS MODERN ECONOMY BRANCH IN STUDENT VIEW:: PROBLEMS, PROSPECTS AND VALUE SYSTEM - V. Bakshaeva, Elena; A. Ganaeva, Elena; I. Tararina, Larisa; M. Sharafutdinova, Maria; A. Rybolovleva , Alla; A. Novikov, Aleksandr; V. Novikova, Elena (Revista Gênero e Interdisciplinaridade, 2021)
The most important trend in the development of the world economy in recent years has been the unprecedented growth of tourism influence and its role, which today is one of the most dynamically developing sectors of the economy. Being aware of all the economic and socio-cultural advantages, the development of tourism in Russia attracts more and more attention every year. The starting point for the development of tourism in this country was the creation of regional programs for the development of this industry. The aim of the study is to identify innovative methods for the development of aesthetic tourism; to determine the role of the creative orientation of the individual in the development of this type of tourism in the representation of students. Research methods: as a research method, a questionnaire survey was used to identify the peculiarities of attitudes to aesthetic tourism. Research results: the article describes the knowledge and attitude of the respondents to aesthetic tourism. Social prerequisites and prospects for the development of aesthetic tourism for the development of Russian regions are studied. The novelty and originality of the study lies in the fact that for the first time the phenomenon of aesthetic tourism was investigated. It is revealed that aesthetic tourism is able to influence the socio-cultural and economic sphere of Russian regions, contributing to business development, improving the investment climate, thanks to the development of the regions attractiveness, and creating jobs for many talented and active people. It is shown that aesthetic tourism, from the student point of view, does not require a sufficiently developed infrastructure, which gives an additional opportunity to develop these innovative projects. It is determined that in order to activate the elements of aesthetic tourism, it is necessary to implement it within the framework of creative industries. It is revealed that the use of this form of tourism is relevant and profitable from the point of view of the current economic situation in Russia and based on the characteristics of the regions, available resources, social and cultural. It is shown that, according to students, aesthetic tourism connects creativity and business; there is a method of creative industries as the most important components of the economy (both at the national level, and at the regional and municipal level). It is determined that in Russia there are some market participants interested in aesthetic tourism, but support for the idea of a creative economy is still only from the bottom - from public organizations and business. It is shown that it is possible to develop aesthetic tourism due to the specifics of creative industries, thereby strengthening the economic component of the tourism industry. Practical significance: The data obtained in this work can be used in the economic sphere, tourism, as well as for further theoretical development of this issue